Ortsaufgelöste Simulation des externen Stofftransports in komplexen Katalysatorträgergeometrien. Issue 4 (26th February 2014) - Heidig, Tobias; Zeiser, Thomas; Schwieger, Wilhelm; Freund, Hannsjörg; Klemm, Elias; Sauer, Jörg
<x xml:space="preserve">Abstract</x> The design of tailor‐made innovative catalyst support structures enables improved reactor performance by freely tunable fluid flow and mass transport characteristics. Numerical geometry generation, fluid flow simulation and particle tracking for mass transport investigation allow for the required understanding of the structure‐transport relationship. Particle tracking, as simulation of the movement of many tracer particles, is costly. This article presents simulation methods including numeric and algorithmic challenges.